Child domestic labour in Pakistan: a narrative review - Salman Abdul Ghaffar, Raahim; Enam, Kishwar (Journal of the Pakistan Medical Association, 2025)
Child domestic workers are children who are hired to work in households by the ownershousehold chores. In 1996, up to 8.3% of all child labour cases in Pakistan involved domestic chores Poverty is one of the most common and significant factors for child domestic labour in Pakistan. Studies have shown that if the parents are uneducated or do not value education, there is a high likelihood of children being involved in child domestic labour. Girls make up a large portion of child domestic workers compared to boys, and are more affected by child domestic labour. The victims of child domestic labour have to bear physical, mental and sometimes sexual abuse from the employers. Given these conditions, child domestic labour can be considered a form of modern-day slavery, with victims being children who may not be aware of their rights. Key Words: Child labour, CDL, Child abuse, Physical health.